The role of hematopoietic stem cell transplantation in SP110 associated veno‐occlusive disease with immunodeficiency syndrome. Issue 3 (1st March 2013) - Ganaiem, Hammam; Eisenstein, Eli M.; Tenenbaum, Ariel; Somech, Raz; Simanovsky, Natalia; Roscioli, Tony; Weintraub, Michael; Stepensky, Polina
Abstract Background Veno‐occlusive disease with immunodeficiency (VODI) is an autosomal recessive disorder of combined immunodeficiency (CID) and hepatic injury. Hematopoietic stem cell transplantation (HSCT) – the only definitive treatment for CID – appeared to have a high rate of complications in a previous report. In this study, we describe a new group of patients with VODI highlighting further clinical and immunologic aspects of this disease and re‐evaluating the effectiveness of HSCT for the treatment of this disorder. Patients and methods Review of clinical data, immunologic features, molecular studies, treatment, and final outcome of eight kindred members with VODI. Results The patients described had clinical and immunologic findings consistent with VODI. The molecular studies revealed a new mutation in the SP110 gene. HSCT was carried out in five patients and was successful in three. Conclusions The diagnosis of VODI should be considered in all patients regardless of ethnicity with a severe combined immunodeficiency (SCID)‐like presentation, especially with a normal mitogen response, or with signs of hepatic injury. VODI is a primary immune deficiency, which can be successfully corrected by bone marrow transplantation if applied early in the course of disease using appropriate conditioning.